Seleksi Dan Pembinaan Peserta MTQ Dalam Upaya Melahirkan Generasi Qur’ani Berprestasi Di Kecamatan Wonoayu - Murtadlo, Ahmad; Yuliastutik, Yuliastutik (At Taawun Bangun Bangsa, 2025)
This study aims to enhance the quality of santri through the selection and mentoring process of Musabaqah Tilawatil Qur’an (MTQ) participants in Wonoayu District as a strategy to produce a Qur’anic generation with strong character and competitiveness. The main challenges include limited regeneration at the village level, unequal access to training facilities, and unsustainable coaching programs. The study employs an Asset-Based Community Development (ABCD) approach combined with SWOT analysis to identify strengths, weaknesses, opportunities, and challenges. Data were collected through interviews, observations, and documentation, then analyzed using a descriptive qualitative method with source triangulation. The findings reveal that active involvement of the community, trainers, and Islamic educational institutions serves as a key asset supporting program success. Approximately 80% of participants who underwent intensive training showed improvement in technical skills and self-confidence, based on trainers’ evaluations and activity records. Additionally, several TPQ initiated cross-village joint training programs to strengthen Qur’anic social networks. These findings confirm that synergy among local actors through optimizing community assets can create sustainable and contextual coaching models. In conclusion, MTQ activities in Wonoayu function not only as a religious competition but also as a medium for community empowerment and Islamic character education relevant to today’s youth.